The influence of higher order thinking skills, vocabulary mastery and reading motivation on reading comprehension achievement - Titik Sholihah (LingTera, 2019)
This research aims at finding out the influence of Higher Order Thinking Skills (HOTSs), vocabulary mastery and reading motivation on reading comprehension achievement among State SMP Students in Magelang Regency. This research was an ex post facto design. The sampling technique was the proportional cluster random sampling. The research instruments were tests and a questionnaire. The data were analyzed using the multiple regression analysis continued by the partial correlation. The result of the multiple regressions indicates that HOTSs, vocabulary mastery and reading motivation influence reading comprehension achievement with the F=236.709 which means that significantly on reading comprehension achievement. The contribution of HOTSs on reading comprehension achievement is 38.7%, vocabulary mastery is 50.3%, and reading motivation is 8.2%.